Educational service centers in Connecticut - Yulo, Frank R. (Connecticut State Dept. of Education, 1977)
Book Title: Educational service centers in Connecticut Place: Hartford SCSU Faculty Scholar Award
Keywords: Connecticut; Teachers; In-service training; Regional Educational Service Centers in Connecticut; Instructional materials centers; Special education; award_winner; dept.edu

Wellsprings of Anticipatory Democracy: An Eco-Systems Preface to the Quality of Life - Clark, Jere W. (Division of Technology and Environmental Education U.S. Office of Education, 1974)
Keywords: Economics; Methodology; Economics; Study and teaching; dept.edu; faculty_collection

Songs in Action - Gelineau, R. Phyllis (McGraw-Hill Book Co., 1974)
Keywords: Instruction and study; Children's songs; School music; dept.edu; faculty_collection

Experiences in Music - Gelineau, R. Phyllis (McGraw-Hill Book Co, 1970)
Keywords: Instruction and study; School music; dept.edu; faculty_collection

Book Review: Handbook of curriculum evaluation. edited by arieh lewy. new york: longman, inc., 1977. 306pp: - Davis, Harold S (NASSP Bulletin, 1978)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/086-446-916-320-298 tex.type: [object Object]
Keywords: book.review; dept.edu

Preparing principals for action, leadership - Davis, Harold S (NASSP Bulletin, 1974)
Both the curricula and methodology of preparing principals is the subject of this article. Describing procedures that work, it will interest principals as well as professors of school administration. © 1974, Sage Publications. All rights reserved.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/028-405-703-165-795 tex.type: [object Object]
Keywords: dept.edu